Understanding and Enhancing Chinese TEFL Teachers’ Motivation for Continuing Professional Development Through the Lens of Self-Determination Theory - Yang, Jie (Frontiers in Psychology, 2021)
Teachers’ continuing professional development (CPD) is a dynamic process that coordinates teachers’ external behavior and internal states. Most teachers participate in varied forms of CPD activities either voluntarily or contractually. The more motivated teachers are to engage in CPD, the more likely they achieve professional and personal growth. Against this backdrop, the current study, adopting the framework of self-determination theory (SDT), sought to investigate the types and levels of Chinese college TEFL (Teaching English as a Foreign Language, hereafter TEFL) teachers’ motivation towards CPD. The questionnaire survey was administered to 402 academics who taught the English language in diverse universities in China. The quantitative analysis showed that teachers exhibited stronger identified regulation and intrinsic motivation than external regulation. Specifically, the exploratory factor analysis identified five motivational orientations: inner-directed academic improvement and cognitive interest, academic self-fulfillment and obligation, academic and social responsibility, social recognition and promotion, lacking the intention for CPD, which corresponded to the SDT motivation continuum. To triangulate, further interviews were conducted with four TEFL teachers. The findings of the qualitative analysis—the thematic analysis through Nvivo (Version 12) on the open-ended question and the interviews, revealed that teachers’ struggles in CPD were mainly concerned with the school-related, CPD-related, and teacher-related problems. Moreover, a big gap between teachers’ needs and contextual support was found to be bridged. Based on the findings, this study proposed that social conditions should support teachers’ basic psychological needs in order to sustain and enhance TEFL teachers’ motivation for CPD.